An Investigation of Comprehension Processes Among Adolescent English Learners With Reading Difficulties. Issue 2 (April 2017) - Lesaux, Nonie K.; Harris, Julie Russ
Abstract : This mixed-methods study examines the reading skills and processes of early adolescent Latino English learners demonstrating below-average reading comprehension performance ( N = 41, mean age = 13 years). Standardized measures were used to estimate participants' word reading and vocabulary knowledge, and interviews were conducted to examine reading comprehension processes used when reading and responding to a grade-level passage. Results demonstrated participants' adequate word-reading skills and below-average vocabulary knowledge, coupled with seemingly active engagement in comprehension processes, including paraphrasing and inference making. Reading comprehension processes, as reported by participants, did not appear to benefit comprehension unequivocally, and participants' descriptions of the passage indicated imprecise comprehension, including substantive misunderstandings. These results are interpreted in light of extant reading research and theories, suggesting that for reading comprehension processes to support effective construction of a rich mental representation of the text, they must be accompanied by relevant background knowledge and language skills.